Patients with Fuchs Endothelial Dystrophy and Cataract Undergoing Descemet Stripping Automated Endothelial Keratoplasty and Phacoemulsification with Intraocular Lens Implant: Staged versus Combined Procedure Outcomes. (12th May 2015) - Sykakis, Evripidis; Lam, Fook Chang; Georgoudis, Panagiotis; Hamada, Samer; Lake, Damian
Abstract : Purpose . To compare the surgical outcomes of staged and combined phacoemulsification with intraocular lens implant (phaco+IOL) and Descemet stripping automated endothelial keratoplasty (DSAEK) in patients with Fuchs' endothelial dystrophy and cataract. Setting . Corneoplastic Unit and Eye Bank, Queen Victoria Hospital, East Grinstead, UK. Methods . Retrospective study of patients who had combined phaco+IOL and DSAEK (group 1) or phaco+IOL followed within 2 months by DSAEK (group 2). Patients who had previous eye surgery or any other ocular comorbidities were excluded. Results . There were 28 eyes in group 1 and 31 in group 2. There were no significant differences in the demographics and corneal tissue characteristics of the two groups. The endothelial disc dislocation and rebubbling rate within 1 week in group 1 was 21.42% and in group 2 was 3.2%P = 0.04, while the endothelial cell density at 12 months was1510 ± 433 for group 1 and1535 ± 482 for group 2P = 0.89 . The mean 12-month logMAR visual acuity was0.28 ± 0.24 for group 1 and0.33 ± 0.15 for group 2P = 0.38 . Conclusions . Although the combined procedure seems to be associated with a higher complication rate the final outcomes seem to be similar to both methods.